2007
DOI: 10.1128/iai.01412-06
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase Controls NF-κB Transcriptional Activation and Tumor Necrosis Factor Alpha Production through RelA Phosphorylation Mediated by Mitogen- and Stress-Activated Protein Kinase 1 in Response toBorrelia burgdorferiAntigens

Abstract: The interaction of Borrelia burgdorferi, the causative agent of Lyme borreliosis, with phagocytic cells induces the activation of NF-B and the expression of proinflammatory cytokines including tumor necrosis factor alpha (TNF-␣). B. burgdorferi-induced TNF-␣ production is also dependent on the activation of p38 mitogenactivated protein (MAP) kinase. The specific contribution of these signaling pathways to the response of phagocytic cells to the spirochete and the molecular mechanisms underlying this response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 56 publications
(69 reference statements)
7
85
0
Order By: Relevance
“…16 In CD4+ T-cells, the MAPK pathway is induced on activation of the TCR and regulates cytokine gene transcription. 17 Alternatively, TLR4 expressing CD4+ T-cells signal via the MAPK pathway to induce tonic inhibitory signals in mice.…”
Section: Discussionmentioning
confidence: 99%
“…16 In CD4+ T-cells, the MAPK pathway is induced on activation of the TCR and regulates cytokine gene transcription. 17 Alternatively, TLR4 expressing CD4+ T-cells signal via the MAPK pathway to induce tonic inhibitory signals in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Excitingly, SCH23390 significantly suppressed RORct expression, whereas SKF83959, a D1-like-R agonist, displayed an opposite effect. Previous studies revealed that stimulation of D1-like-R signalling mediates p38 MAPK activation [6], which then activates NF-jB [7,8], a transcription factor responsible for the transcription of genes implicated in inflammatory processes, in which BATF is a downstream gene of NF-jB signalling [8]. Furthermore, activation of signal transducer and activator of transcription 3 by Gas [24] can facilitate the induction of BATF [25].…”
Section: Discussionmentioning
confidence: 99%
“…Given that asthma shares certain disease aetiology similarities with EAE and type 1 diabetes, it is plausible to assume that the D1-like-R antagonist prevents Th17-mediated asthma as well. Furthermore, D1-like-R couples with the Gas class of G proteins, and its agonists mediate p38 mitogen-activated protein kinase (MAPK) activation [6], which then activates nuclear factor-jB (NF-jB) [7,8], a crucial transcription factor responsible for BATF expression [9]. We therefore hypothesized that D1-like-R signalling induces BATF activation, and thus enhances Th17 function to promote the development of allergic asthma.…”
mentioning
confidence: 99%
“…The data represent the average protein levels Ϯ SDs from at least three independent experiments, which were analyzed by the Student t test. *, P Ͻ 0.05; ***, P Ͻ 0.001. of both AP-1 and NF-B, which leads to transcriptional activation (49,50), whereas ERK phosphorylation of AP-1 has only a stabilizing effect (51) and no direct activity on NF-B has been described. ERK can initiate NF-B signaling by activation of RSK-or mitogen and stress-activated protein kinase-related phosphorylation of the NF-B inhibitor, IB␣ (52,53).…”
Section: Discussionmentioning
confidence: 99%